2011
DOI: 10.1080/13658816.2010.517755
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of intersections in linear habitat on spatial distribution and local population density

Abstract: Many species in human-dominated landscapes find their habitat in linear elements, such as road verges, hedgerows and ditches. Local concentrations of species have been observed in the intersections of linear elements, but their spatial distribution and local population density in this linear habitat are not well captured by existing theory. Using a simple, spatially explicit individual-based GIS-model simulating hedgerow bird species with different movement abilities, local high population density of our model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A common legacy of such modification, particularly in agricultural environments, is the creation of networks of linear vegetation [ 2 ]; such as hedgerows in Europe [ 3 , 4 ], fencerows in North America [ 5 , 6 ], live fences in southern and central America [ 7 ], and roadside vegetation in Australia [ 8 , 9 ]. In highly modified regions, such linear elements potentially play an important role in biodiversity conservation [ 10 , 11 ]. Hedgerows and arable field margins in European farmland, for example, provide nest and roost sites, food resources and movement pathways for birds [ 4 , 12 ]; while in the Americas, fencerows and live fences provide refuge, foraging resources and movement corridors for diverse assemblages of birds, butterflies, bats and beetles [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common legacy of such modification, particularly in agricultural environments, is the creation of networks of linear vegetation [ 2 ]; such as hedgerows in Europe [ 3 , 4 ], fencerows in North America [ 5 , 6 ], live fences in southern and central America [ 7 ], and roadside vegetation in Australia [ 8 , 9 ]. In highly modified regions, such linear elements potentially play an important role in biodiversity conservation [ 10 , 11 ]. Hedgerows and arable field margins in European farmland, for example, provide nest and roost sites, food resources and movement pathways for birds [ 4 , 12 ]; while in the Americas, fencerows and live fences provide refuge, foraging resources and movement corridors for diverse assemblages of birds, butterflies, bats and beetles [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This ‘intersection effect’ (see Fig 1 ) in hedge networks has been supported by observations of greater species richness of corridor-dependent bird species at or near intersections [ 24 ]. Van Langevelde and Grashof-Bokdam [ 10 ] modeled bird movement in hedgerow networks and found that species with limited movement ability occurred at higher densities at intersections than in linear strips. They concluded this was likely due to the species’ ability to recolonise intersections more quickly following mortality of other individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-cutting theme in this issue is human-wildlife interactions and conflicts in space and time (Loraamm andDowns this issue, Saito et al 2016, Zengeya andMurwira 2016), a topic also covered in previous special issues (David Walter et al 2011, van Langevelde andGrashof-Bokdam 2011). Further linkages between humans and ecological processes are assessed by Fagúndez and Izco (2016), who explore the use of toponyms as a means of identifying historical vegetation types.…”
Section: Introductionmentioning
confidence: 99%